Ethnic Features and Transformational Processes of Kungirots' of Southern Uzbekistan - Usmonov Murtoz Shodiyevich (Buletin Antropologi Indonesia, 2025)
This article examines the ethnic features and transformational processes of the Kungirots, one of the historically significant ethnographic groups of Southern Uzbekistan. The study analyzes their traditional social organization, cultural identity markers, systems of kinship, and ritual practices, highlighting how these elements have evolved under the influence of socio-economic modernization, migration trends, and political restructuring in the region. Special attention is given to the transformation of communal institutions, intergenerational relations, and cultural continuity mechanisms, as well as to the role of globalization and urbanization in reshaping ethnic identity. By drawing on ethnographic observations, historical sources, and comparative analyses, the research provides a comprehensive understanding of the dynamic nature of the Kungirots’ ethnocultural identity. This article presents the social life, ethnicity and transformational processes of the Uzbek-Kungrad in the Kashkadarya and Surkhandarya regions.